Social capital and mental health in Japan: a multilevel analysis. - Tsuyoshi Hamano (PLoS ONE, 2010)
A national cross-sectional survey was conducted in Japan. This is because the growing recognition of the social determinants of health has stimulated research on social capital and mental health. In recent years, systematic reviews have found that social capital may be a useful factor in the prevention of mental illness. Despite these studies, evidence on the association between social capital and mental health is limited as there have been few empirical discussions that adopt a multilevel framework to assess whether social capital at the ecological level is associated with individual mental health. The aim of this study was to use the multilevel approach to investigate the association between neighborhood social capital and mental health after taking into account potential individual confounders.We conducted a multilevel analysis on 5,956 individuals nested within 199 neighborhoods. The outcome variable of self-reported mental health was measured by the one dimension of SF-36 and was summed to calculate a score ranging from 0 to 100. This study showed that high levels of cognitive social capital, measured by trust (regression coefficient = 9.56), and high levels of structural social capital, measured by membership in sports, recreation, hobby, or cultural groups (regression coefficient = 8.72), were associated with better mental health after adjusting for age, sex, household income, and educational attainment. Furthermore, after adjusting for social capital perceptions at the individual level, we found that the association between social capital and mental health also remained.Our findings suggest that both cognitive and structural social capital at the ecological level may influence mental health, even after adjusting for individual potential confounders including social capital perceptions. Promoting social capital may contribute to enhancing the mental health of the Japanese.